2022
DOI: 10.3389/fragi.2022.1016962
|View full text |Cite
|
Sign up to set email alerts
|

Fly immunity comes of age: The utility of Drosophila as a model for studying variation in immunosenescence

Abstract: The global demographic is shifting towards an aged population (United Nations, 2019). Yet, it is our oldest members of society that are the most vulnerable to infectious disease, reflecting immune system ageing, or "immunosenescence" (Glynn and Moss, 2020;Chen et al., 2021). Immunosenescence has two defining features: heightened susceptibility to pathogens, and increased systemic, basal inflammation (Franceschi, 2000;Zerofsky et al., 2005; Benayoun et al., 2019), which is strongly linked to the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…Previously, it has been demonstrated that aging in Drosophila is accompanied by a considerable increase in the expression of immune-related genes [ 61 , 62 , 63 ]. In order to assess the effect of Yap/Taz inhibitors on inflammatory markers of aging, we compared the expression level of antimicrobial genes ( Attacin-A ( AttA ), Diptericin A ( DptA ), cecropin A1 ( CecA1 )) between treated and control flies of both sexes at the age of 10 and 20 days.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it has been demonstrated that aging in Drosophila is accompanied by a considerable increase in the expression of immune-related genes [ 61 , 62 , 63 ]. In order to assess the effect of Yap/Taz inhibitors on inflammatory markers of aging, we compared the expression level of antimicrobial genes ( Attacin-A ( AttA ), Diptericin A ( DptA ), cecropin A1 ( CecA1 )) between treated and control flies of both sexes at the age of 10 and 20 days.…”
Section: Resultsmentioning
confidence: 99%